The Political Organization under Socialism - Morkūnas, Zigmas (Problemos, 1970)
The author on the basis of V. I. Lenin’s heritage reveals the essence and purpose of the political organisation of society – the system of the proletariat dictatorship under socialism. The essence and purpose of the political organization, its specific structure and function for practical application can be disclosed scientifically proceeding from the analysis of interconditional technological and social conditions of communism or from the analysis of conditions for diverse human requirements as an ultimate end. Application of elements of the system for achieving this goal is as much successful as much effectively this double aim is reached, for so much the control is “economical policy” according to V. I. Lenin or policy as the concentrated expression of economical objects.